Impacts of Reduced Nitrate Supply on Nitrogen Metabolism, Photosynthetic Light-Use Efficiency, and Nutritional Values of Edible Mesembryanthemum crystallinum - He, Jie; Qin, Lin (Frontiers in Plant Science, 2021)
Mesembryanthemum crystallinum (common ice plant), as a nutritious ready-to-eat salad in Singapore, has become popular in recent years. However, basic data about the impacts of NO3– supply on its NO3– accumulation and nutritional quality are lacking. In this study, all plants were first grown indoors hydroponically in 10% artificial seawater with modified full-strength Netherlands Standard Composition nutrient solution for eleven days before being transferred to different reduced NO3– solutions. All plants grew well and healthy after 7 days of treatments. However, plants grown with 3/4N and 1/2N were bigger with higher shoot and root fresh weight, greater leaf number and total leaf area than those of full N, 1/4N and 0N plants. M. crystallinum grown with full N, 3/4 N and 1/4N had similar specific leaf area (SLA) while 0N plants had significantly lower SLA. There were no significant differences in leaf succulence among all plants after 7 days of treatments. However, leaf water content was lower while leaf dry matter accumulation was higher in M. crystallinum after being transferred from full N to 0N for 7 days. Compared to M. crystallinum grown with full N, shoot NO3– concentrations in those being transferred from full N to 3/4N, 1/2N and 1/4N were constant or slightly increased during the treatments. For M. crystallinum after being transferred from full N to 0N, shoot NO3– concentration decreased during the treatment and it was significantly lower compared to other plants. Shoot NO3– accumulation was associated with nitrate reductase activity. After transferring full N to 0N for 7 days, all M. crystallinum had higher chlorophyll content coupled with higher electron transport rate and higher effective quantum yield of PS II while full N plants had higher NPQ. The 0N plants had much higher concentrations of proline, TSS and total ASC than those of other plants. In conclusion, totally withdrawing NO3– from the growth media prior to harvest could be one of the strategies to reduce shoot NO3– concentration and to further enhance nutritional values as concentrations of proline, TSS and ASC were enhanced markedly in M. crystallinum after being transferred from full N to 0N.